Antimicrobial and Cytotoxic Activities of Secondary Metabolites Obtained from a Novel Species of Streptomyces (Bangladesh Pharmaceutical Journal, 2013)
With an aim to isolate actinomycetes having antimicrobial and cytotoxic activities, five colonies of actinomycetes were collected from soils of a vegetable garden of Rajshahi District, Bangladesh and designated as ANTS-1 to ANTS-5. Initial screening for antibacterial activity showed that the isolate ANTS-1 produced potent antimicrobial metabolites in the culture media. The crude ethyl acetate extract obtained from the yeast-extract glucose agar (YEGA) medium showed strong activity against pathogenic bacteria and moderate activity against fungi. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the extract against the test bacteria were in the range of 1-2 ?g/ml and 4-8 ?g/ml, respectively. The LC50 value of the crude extract against brine-shrimp nauplii was only 0.4?g/ml indicating its potent cytotoxic activity. One component of the extract was identified as actinomycin D by interpretation of the spectral data and by comparison with published values. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14485 Bangladesh Pharmaceutical Journal 16(1): 15-19, 2013